PELATIHAN YOGA UNTUK MENINGKATKAN KESEHATAN MENTAL BAGI ANAK-ANAK BERKEBUTUHAN KHUSUS DI YAYASAN SEHATI BALI - Dewi, Gusti Ayu Putu Paramita Sari; Yasa, Ngakan Putu Darma (UNHI Press, 2025)
Yoga training is often used as alternative therapy to alleviate various physical and spiritual ailments through gentle, flexible body movements that promote overall well being. The disabled children at the Sehati Bali Foundation frequently experience high levels of stress, which significantly impacts their mental health. This stress can manifest in unpredictable outbursts, such as screaming without apparent reason, crying, and even throwing objects. Yoga training has numerous benefits, including enhancing an individuals abilities, improving mental health, managing stress and boosting concentration. This community service aims to partner with the Sehati Bali Foundation to provide yoga training specifially designed to improve the mental health and well being of disabled children. The training demonstration was conducted outdoors in the open courtyard of the Sehati Bali Foundation. The yoga training provided wa tailored to the childrens needs, featuring simple and easy to follow movements that allowed them to participate. The community service show positive results, demonstrating that yoga activities can significantly reduce unpredictable behaviors in disabled children, such as screaming, anger outbursts, throwing objects, and crying. Moreover, the yoga training helped these children become more relaxed and receptive, making them more willing to follow instructions that they would normally ignore.